Properties of fly ash and slag blended geopolymer concrete cured at ambient temperature - Deb, Partha; Nath, Pradip; Sarker, Prabir (Research Publications Services, 2013)
The properties of concrete using fly ash based geopolymer as the binder were shown in recent studies. However, most of the previous studies focused on the properties of geopolymer concrete samples cured at high temperature. In this study, fly ash based geopolymer concrete suitable for curing at ambient temperature was designed and some durability properties were investigated. Geopolymer mixtures were prepared with fly ash as the primary binder which was activated by a mixture of sodium silicate and sodium hydroxide solutions. Ground granulated blast furnace slag (GGBFS) was added as 0%, 10% and 20 % of the total binder. Samples were also cast from an ordinary Portland cement (OPC) concrete mixture in order to compare with the properties of geopolymer and OPC concretes. All the concrete samples were ambient-cured (15-20°C) after casting until tested. The tests conducted include compressive strength, drying shrinkage, sorptivity and volume of permeable voids (VPV) test. The strength of the geopolymer concretes enhanced from the early age and continued to develop in similar trend as OPC concrete. Strength increased with the increase of slag in the mixture. The geopolymer concretes showed drying shrinkage, sorptivity and VPV values comparable to those of the control OPC concrete. In general, the results show that it is possible to design fly ash and slag blended geopolymer concrete suitable for ambient curing with similar or better durability properties of conventional OPC concrete.